2006
DOI: 10.1525/jer.2006.1.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Scientists' Perceptions of Organizational Justice and Self-Reported Misbehaviors

Abstract: POLICYMAKERS CONCERNED ABOUT maintaining the integrity of science have recently expanded their attention from a focus on misbehaving individuals to characteristics of the environments in which scientists work. Little empirical evidence exists about the role of organizational justice in promoting or hindering scientific integrity. Our findings indicate that when scientists believe they are being treated unfairly they are more likely to behave in ways that compromise the integrity of science. Perceived violation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 60 publications
5
129
3
2
Order By: Relevance
“…This may lead established scientists to believe that early-career scientists are more likely to engage in QRPs (and thus fit the storybook image less well) than PhD students and established scientists, but studies comparing self-admitted usage of QRPs and misbehavior between scientists of different career-stages have yielded mixed results. Some studies found that younger scientists are more likely to admit to undesirable scientific behavior Tijdink et al, 2014), while other studies found that older scientists are more likely to admit to this kind of behavior (Martinson, Anderson, Crain, & De Vries, 2006;Martinson, Anderson, & de Vries, 2005). Another explanation might be sought in the idea that Ph.D. students represent potential rather than practice, making it easier to imagine them as matching the ideal.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead established scientists to believe that early-career scientists are more likely to engage in QRPs (and thus fit the storybook image less well) than PhD students and established scientists, but studies comparing self-admitted usage of QRPs and misbehavior between scientists of different career-stages have yielded mixed results. Some studies found that younger scientists are more likely to admit to undesirable scientific behavior Tijdink et al, 2014), while other studies found that older scientists are more likely to admit to this kind of behavior (Martinson, Anderson, Crain, & De Vries, 2006;Martinson, Anderson, & de Vries, 2005). Another explanation might be sought in the idea that Ph.D. students represent potential rather than practice, making it easier to imagine them as matching the ideal.…”
Section: Discussionmentioning
confidence: 99%
“…One way of creating an environment that is less conducive of research misconduct is to be sensitive to the needs of the researchers and their sense of organizational justice. In the survey by Martinson et al, selfreported scientific misconduct by scientists correlated positively with their perceptions of distributive and procedural injustice (Martinson et al 2006). Another survey by Keith-Spiegel et al showed that researchers expect fairness and respect from the Institutional Review Boards (IRBs) (Keith-Spiegel et al, 2006).…”
Section: "Systems Approach" To Primary Preventionmentioning
confidence: 99%
“…Two more studies analysed effects of experienced nonreciprocity at work on intentions to leave one's job prematurely and observed strong, consistent associations (Hasselhorn et al, 2004;Siegrist et al, 2007). The question of whether the frustration of work-related rewards increases the risk of norm-breaking behaviour has been studied in the context of a large anonymous survey of several thousand early-career and mid-career researchers in the United States (Martinson et al, 2006). It was found that a high effort-reward imbalance ratio was related to an increased probability of scientific misbehaviour in early-career, but not in mid-career scientists.…”
Section: Brief Summary Of Empirical Evidence On Health-adverse Effectsmentioning
confidence: 99%